1998
DOI: 10.1073/pnas.95.11.6187
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of GTP on rab11 is required for the direct delivery of transferrin from the pericentriolar recycling compartment to the cell surface but not from sorting endosomes

Abstract: Rab11 is a small GTP-binding protein that in cultured mammalian cells has been shown to be concentrated in the pericentriolar endosomal recycling compartment and to play a key role in passage of the recycling transferrin receptor through that compartment [Ullrich, O., Reinsch, S., Urbé, S. To obtain insights into the site(s) of action of rab11 within the recycling pathway, we have now compared the effects on recycling at 37°C of overexpression of wild-type rab11 and various mutant forms of this protein in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
410
5
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(469 citation statements)
references
References 36 publications
49
410
5
1
Order By: Relevance
“…Rather, some colocalization between the internal pool of Langerin, as revealed by the anti-lag mAb, and the LC marker CD1a was evident in the pericentriolar area ( Figure 1D). In another study carried out in the same cell type, we demonstrated that intracellular CD1a also colocalizes with Rab11 (Salamero et al, 2001), a small GTPase that specifically associates with the membrane of the endosomal recycling compartment (ERC) (Ullrich et al, 1996;Ren et al, 1998). Steady-state internal Langerin colocalized strongly with Rab11 in the ERC ( Figure 1E) but poorly with EEA1, a marker of the early/sorting endosomes ( Figure 1F) (Simonsen et al, 1998;Christoforidis et al, 1999;McBride et al, 1999 …”
Section: Langerin Is Associated With Rab11mentioning
confidence: 91%
“…Rather, some colocalization between the internal pool of Langerin, as revealed by the anti-lag mAb, and the LC marker CD1a was evident in the pericentriolar area ( Figure 1D). In another study carried out in the same cell type, we demonstrated that intracellular CD1a also colocalizes with Rab11 (Salamero et al, 2001), a small GTPase that specifically associates with the membrane of the endosomal recycling compartment (ERC) (Ullrich et al, 1996;Ren et al, 1998). Steady-state internal Langerin colocalized strongly with Rab11 in the ERC ( Figure 1E) but poorly with EEA1, a marker of the early/sorting endosomes ( Figure 1F) (Simonsen et al, 1998;Christoforidis et al, 1999;McBride et al, 1999 …”
Section: Langerin Is Associated With Rab11mentioning
confidence: 91%
“…15, November 2004TGN to the plasma membrane (Chen et al, 1998), and from endosomes to the plasma membrane (Ren et al, 1998) and to the TGN (Wilcke et al, 2000). A constitutively active rab8 mutant was found to interfere specifically with AP-1B localization and function, disturbing basolateral sorting (Ang et al, 2003).…”
Section: In Vitro Formation Of Recycling Vesiclesmentioning
confidence: 98%
“…In a similar in vitro assay by using CHO cells, endosome-derived vesicles containing transferrin receptor and GLUT4 were generated by a BFA-insensitive but neomycinsensitive mechanism (Lim et al, 2001). Because endocytic proteins had been internalized at 15°C, a temperature at which transport from sorting to recycling endosomes is blocked (Ren et al, 1998;, the starting compartment was predominantly sorting endosomes and the vesicles generated thus might have represented the fast recycling pathway.…”
Section: Ap-1a/clathrin Coats Mediate Receptor Recyclingmentioning
confidence: 99%
“…40,58,59,62 Transferrin trafficking has been extensively studied and shown to move through the early endosome to the PNRE. 76,77 The recycling of transferrin through the PNRE requires the coordinated interactions of several small GTPases (Rab5, Rab4, and Rab11) that direct the movement and fusion of early endosomes to the PNRE compartment. 77 The colocalization of CPV and AAV2 with transferrin has suggested the potential involvement of the PNRE in the processing of these viruses.…”
Section: Receptor-mediated Endocytosis Of Aavmentioning
confidence: 99%